anuu wrote:

The answer choices given in the online test are:

-2, 2, -1,1 and cannot be determined.

Can you pls explain the last line where you have equated the two equations..

i do understand that u have replaced x with x+2 in the equation 2x^2+bx+c

thus 2x^2+bx+c = 2 (x+2)^2 + b(x+2) +c

why are we equating the two equations ? and the increase in 12 is not accounted for? Can you pls explain the concept?

Regards,

Anu

Oh, I missed the "+12" part. It should be there.

\(2(x+2)^2+b(x+2)+c=2x^2+bx+c+12\)

\(2(x^2+4+4x)+bx+2b+c=2x^2+bx+c+12\)

\(2x^2+8+8x+bx+2b+c=2x^2+bx+c+12\)

\(8+8x+2b=12\)

\(8x+2b=4\)

\(4x+b=2\)

\(x=\frac{2-b}{4}\)

So, x is dependent on the value of "b" and thus cannot be determined.

If b=0; x=1/2; will satisfy the condition

If b=2; x=0; will satisfy the condition

If b=1002; x=(2-b)/4= (2-1002)/4=-250 will satisfy the condition.

Thus, there is no fixed value of x.

Please let me know if something is not clear.

_________________

~fluke

GMAT Club Premium Membership - big benefits and savings